Elaborating Indigenous Science Content into Science Learning Process: A New Science Instructional Model to Develop Students’ Local Wisdom-Based Characters and Higher Order Thinking Skills - Suastra, I Wayan; Rapi, Ni Ketut; Yasa, Putu; Arjana, I Gede (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Character building becomes an essential part in the science learning process to prepare the students as the next generations of our nations. This study aims to develop a valid, practical, and effective learning model combined with indigenous science content for junior high school students in developing local wisdom-based characters and high-order thinking skills. This research is a a research and development (R & D) approach with the Borg and Gall model involving 36 junior high school science teachers (72 teachers). The research instrument were a character questionnaire as well as a test of problem-solving, critical and creative thinking tests, along with an assessment rubric to measure the depth of students' cognitive abilities. From the results of the learning model trial, it was found that there are eight characters based on Balinese local wisdom that can be developed in science learning for junior high school students namely religious, being honest (satyam), tolerance (tat twam asi), responsible (sesana/swadharma), curious, jengah, hardworking and generous, caring and friendly with nature. Conceptually, the core stages of the junior high school science learning model to develop Balinese local wisdom based characters include: initial exploration, investigation from various perspectives, elaboration, and confirmation and reinforcement. The stages in the science learning model that develop characters based on local wisdom provide opportunities for teachers to improve students' cognitive abilities, especially in the realm of higher-order thinking skills.